FORMULATION AND DEVELOPMENT OF MODIFIED PROPRANOLOL HCL TABLET - PRAFULLA S. CHAUDHARI; P. SHANMUGASUNDARAM (International Journal of Pharma and Bio Sciences, 2014)
A co-processed excipient was prepared from Tamarind seed polysaccharide (TSP) and mannitol in using direct compression as well as wet and dry granulation. The effect of the ratio of the two components, percentage of lubricant and particle size on the properties of the prepared co-processed excipient has been investigated. Optimal physicochemical properties of the excipient, from a manufacturing perspective, were obtained using a co-processed mannitol- TSP (2:8 w/w) mixture prepared by wet granulation. Disintegration time, crushing strength and friability of tablets produced by co-processed mannitol- TSP, using magnesium stearate as a lubricant, were found to be independent of the particle size of the prepared granules. The inherent binding and disintegration properties of the compressed co-processed mannitol- TSP are useful for the formulation of poorly compressible, low and high strength active pharmaceutical ingredients. The ability to co-process Tamarind seed polysaccharide (TSP) with crystalline mannitol allows TSP to be used as a valuable industrial pharmaceutical excipient. The aim of present study was to formulate and evaluate an oral sustained release tablet of Propranolol hydrochloride to increase therapeutic effect, reduced frequency of administration and improved patient compliance. Propranolol HCl tablet was formulated by using co-processed excipients Tamarind seed polysaccharide and mannitol. Formulations were prepared by varying the polymer concentration. The optimized formulations were subject to stability testing as per ICH guidelines.